2019
DOI: 10.1155/2019/8151582
|View full text |Cite
|
Sign up to set email alerts
|

Modified Traffic Flow Model with Connected Vehicle Microscopic Data for Proactive Variable Speed Limit Control

Abstract: Most previous prediction based Variable Speed Limit (VSL) control strategies focused on improving traffic mobility based on the macroscopic traffic data. Nowadays, the emerging technologies provide access to the microscopic traffic flow data, which better captures the details of traffic flow dynamics in the VSL controlled environment. Thus, in this paper, the microscopic traffic flow data were utilized as a supplement to predict the evolutions of traffic flow parameters. The proposed VSL control algorithm adop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Besides the direct application of VSL on traffic system, it is also introduced into micro-and mesotraffic flow model [17,18] and other optimization models [19][20][21][22]. Abdel et al used microscopic simulation models to analyze the effects of different speed limit strategies on alleviating and improving road safety [17].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides the direct application of VSL on traffic system, it is also introduced into micro-and mesotraffic flow model [17,18] and other optimization models [19][20][21][22]. Abdel et al used microscopic simulation models to analyze the effects of different speed limit strategies on alleviating and improving road safety [17].…”
Section: Literature Reviewmentioning
confidence: 99%
“…e improved model reduces the speed prediction accuracy error and improves the performance of the system [19]. Alasiri used microscopic simulation software to combine the cell transmission model (CTM) and variable speed limit strategy to verify the effectiveness of the robust VSL controller [20].…”
Section: Literature Reviewmentioning
confidence: 99%
“…From the literature review, it was found that the operational efficiency or capacity was used as the main optimization objective while traffic safety was rarely considered. Besides, there was a new trend that the connected vehicles and/or V2X (vehicle to vehicle, vehicle to infrastructure, and others) were considered increasingly which greatly influenced the operation environment [17,18].…”
Section: Literature Reviewmentioning
confidence: 99%
“…IoV (Vehicle Internet), is the inevitable convergence between the mobile Internet for vehicles and IoT. When in a vehicular network human control is removed by autonomous vehicles; they cooperate efficiently thus controlling the flow of traffic on the roads [ 2 ]. Visionaries predict that autonomous vehicles behave much better than human drivers, which will allow controlling more traffic in less time, producing less pollution and generating greater comfort for passengers [ 3 ].…”
Section: Introductionmentioning
confidence: 99%